Impact of Peripartum Nutritional Supplementation on Thyroid Hormones, Metabolites and Reproductive Peridata in Jafarabadi Buffaloes - Vala, KB; Dhami, AJ; Kavani, FS; Bhanderi, BB; Parmar, SC (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Forty advanced pregnant Jafarabadi buffaloes of 2-4 parity were divided into two equal groups, viz., control and treatment (n = 20 each). The animals of control group were maintained on routine farm feeding schedule and those under treatment group were subjected to additional oral supplements daily with 50 g of chelated mineral mixture and 150 g of bypass fat along with concentrates for 6 weeks prepartum till 2 weeks postpartum, and then bypass fat was given @ 15 g/litre of milk produced till 60 days postpartum. All the buffaloes were subjected to blood collection on day -45, -30, -7, 0, 7, 15, 30, 45 and 60 peripartum. Postpartum animals were followed at weekly interval by per rectal palpation and ultrasonographically for uterine involution, first postpartum estrus and conception. The overall mean blood glucose of prepartum period increased significantly (p<0.01) on the day of calving and reduced back to prepartum levels within next 7 days postpartum in both the groups. The buffaloes supplemented with peripartum nutrients had significantly (p<0.01) higher blood glucose levels than the control group. The mean plasma total protein (7.96 ± 0.04 g/dl) and thyroid hormones T3 (1.44 ± 0.05 ng/ml) and T4 (28.25 ± 0.86 ng/ml) were found to be within the normal range, and did not vary between sampling days or between groups. The peripartum supplementation of bypass fat did not influence the levels of plasma total cholesterol. However, the levels of β-hydroxybutyrate (BHBA) and non-esterified fatty acids (NEFA) tended to be higher in control than treatment group at most of the peripartum intervals. The period of uterine involution (32.75 ± 0.57 vs 37.00 ± 0.56 days) and service period (107.10 ± 4.43 vs 133.65 ± 6.04 days) were significantly (p<0.05) shorter with higher postpartum fertility (85 vs 50% CR) in nutrient supplemented than control group. It was concluded that peripartum bypass fat and mineral supplementation prevented negative energy balance and/or ketosis and improved postpartum fertility in high yielding Jaffrabadi buffaloes.